The response of Antarctic ice volume, global sea-level and southwest Pacific Ocean circulation to orbital variations during the Pliocene to Early Pleistocene - Patterson, Molly O'Rourke (11698477) (2014)
This thesis investigates orbitally-paced variations in the extent of East Antarctic Ice Sheet (EAIS), and the “downstream” influence of these ice sheet variations on ocean circulation and sea level variability during the Pliocene and Early Pleistocene - a time period characterised by a major global cooling step that culminated in the development of a bipolar glaciated world. Three unique records are examined from (1) the Antarctic margin, (2) the southwest Pacific Ocean, and (3) shallow-marine sedimentary strata exposed in Wangnaui Basin, New Zealand. The Integrated Ocean Drilling Program (IODP) Site U1361 recovered a continuous sedimentary Early Pliocene to Early Pleistocene (4.3 to 2.0 Ma) record from the lowermost continental rise on the Wilkes Land margin offshore of the EAIS. A facies model and stratigraphic framework were developed that allowed for the identification of glacial advances (massive and laminated mudstones) and retreats (diatom-rich mudstones) across the continental shelf, with evidence for prolonged retreats spanning several glacial to interglacial cycles throughout the Pliocene. These cycles are followed by an extensive Early Pleistocene interval (~2.6 Ma) of diatom-rich mudstone with evidence for reworking by bottom currents, interpreted to be the consequence of downslope density currents associated with increased sea ice production after 2.6 Ma. Frequency analysis on Iceberg Rafted Debris (IBRD) from Site U1361 reveals that under an Early Pliocene warm climate state (4.3 to 3.3 Ma), that ice discharge off the EAIS occurred in response to climate change paced by the 40-kyr cycles of obliquity. Whereas, the colder climate state of Late Pliocene to Early Pleistocene (3.3 to 2.0 Ma) resulted in a transferral of orbital variance to 20-kyr-duration, precession-dominated variability in IBRD preceding the development of a more stable marine-based margin of the EAIS at ~2.6 Ma, which is hypothesized to reflect the declining influence of oceanic forcing as the high-latitude Southern Ocean cooled thereby increasing the seasonal duration and extent of sea-ice. The precession-paced influence on IBRD and ice volume variability of the EAIS was strongly modulated by 100-kyr-eccentricity, which is expressed lithologically in cycles of two alternating lithofacies 1) diatom-rich mudstones and 2) massive and laminted mudstones in the Site U1361 record. A compilation of benthic stable isotope records from Ocean Drilling Program (ODP) Site 1123 in the southwest Pacific Ocean was also developed. The δ18O record identified a 40-kyr obliquity pacing, consistent with other benthic δ18O records globally for this time period, thus allowing for an orbitally-tuned timescale to be developed for this site. Long-term trends in both the δ18O and δ13C records at ODP Site 1123 coincide with major developments of the Antarctic Ice Sheet and Northern Hemisphere glaciation at 3.33 Ma and ~2.6 Ma respectively. A gradual reduction in the deep water δ13C gradient between the southwest Pacific (ODP Site 1123) and equatorial Pacific (ODP Site 849) between 3.33 and 2.6 Ma coincides with expansion of the Antarctic Ice Sheet, enhanced Antarctic Bottom Water (AABW) production, invigorated atmospheric zonal circulation in the southern hemisphere mid-latitudes, and increased meridional sea surface temperature (SST) gradients in the Pacific Ocean. Finally, a shallow-marine, continental margin stratigraphic section from the Turakina River Valley in the Wanganui Basin, New Zealand, was used to record local sea-level changes, dominated by orbitally-driven, global glacio-eustasy, during the mid-Pliocene interval (3.2 to 3.0 Ma). This interval was selected as it precedes the build-up of significant Northern Hemisphere Ice Sheet, thus allowing for an independent assessment of the orbtial-scale variability of Antarctic Ice Sheet volume. Grain size based proxy of percent mud was employed to reconstruct paleobathymetric changes, which displayed 100-kyr cycles consistent with ~20 m variations in local water depths during the mid-Pliocene. Combined with IBRD record from Site U1361, this reconstruction suggests that the marine margins of East Antarctica varied at orbital timescale, and provided a significant contribution to global eustatic sea-level variations during the mid Pliocene (consistent with global mean sea-level estimates of up to ~+20 m above present from related studies).